2020
DOI: 10.1080/02813432.2020.1802139
|View full text |Cite
|
Sign up to set email alerts
|

Effects of replacing PSA with Stockholm3 for diagnosis of clinically significant prostate cancer in a healthcare system – the Stavanger experience

Abstract: Objective: To describe early experience of replacing PSA with Stockholm3 for detection of prostate cancer in primary care. Design and methods: Longitudinal observations, comparing outcome measures before and after the implementation of Stockholm3. Setting: Stavanger region in Norway with about 370,000 inhabitants, 304 general practitioners (GPs) in 97 primary care clinics, and one hospital. Intervention: GPs were instructed to use Stockholm3 instead of PSA as standard procedure for diagnosis of prostate cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 20 publications
0
17
1
1
Order By: Relevance
“…Other factors than a FH of PCa, age and SNPs could be coupled together to create a predictive test for PCa diagnosis. Recently the Stockholm 3 test, which contains risk SNPs, plasma protein biomarkers and clinical variables, has shown promising results in risk stratifying patients for PCa in a screening setting and thereby avoiding unnecessary biopsies, while maintaining high sensitivity for clinically significant PCa [45–47].…”
Section: Discussionmentioning
confidence: 99%
“…Other factors than a FH of PCa, age and SNPs could be coupled together to create a predictive test for PCa diagnosis. Recently the Stockholm 3 test, which contains risk SNPs, plasma protein biomarkers and clinical variables, has shown promising results in risk stratifying patients for PCa in a screening setting and thereby avoiding unnecessary biopsies, while maintaining high sensitivity for clinically significant PCa [45–47].…”
Section: Discussionmentioning
confidence: 99%
“…This management may also lead to a reduction in healthcare costs. It has been estimated that direct healthcare costs decreased by 23-28% per male studied [87].…”
Section: Stockholm3 Modelmentioning
confidence: 99%
“…STHLM3 is a risk-based model for PC screening that combines 232 SNPs, a combination of plasma protein biomarkers (PSA, iPSA, fPSA, hK2, beta-microseminoprotein and macrophage inhibitory cytokine 1) and clinical variables (family history, age, prostate exam and previous biopsies) [ 153 ]. Studies have found that this model performed better than PSA alone for the detection of high-risk PC, exhibiting its potential to improve PC diagnosis by significantly reducing the number of unnecessary biopsies taken, while also preserving the same sensitivity to diagnose clinically significant PC [ 153 , 154 , 155 , 156 , 157 ].…”
Section: Techniques To Improve the Diagnostic Accuracy Of Pcmentioning
confidence: 99%